2003
DOI: 10.1086/367940
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Foraging Mode and Arid Adaptation on the Basal Metabolic Rates of Burrowing Mammals

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Accepted 10/1/02 The University of Chicago Press ABSTRACTTwo competing but nonexclusive hypotheses to explain the reduced basal metabolic rate (BMR) of mammals that live and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 109 publications
4
30
0
Order By: Relevance
“…In support of the high-temperature selection hypothesis, several studies of both mammals (e.g., McNab and Morrison 1963;McNab 1979;Hinds and MacMillen 1985;White 2003) and birds Williams 2000, Tieleman et al 2003) have reported lower BMR in hot deserts. However, as noted above, hot deserts also have low precipitation and low primary productivity.…”
Section: Predictors Of Body Mass Bmr and Mmrmentioning
confidence: 93%
See 3 more Smart Citations
“…In support of the high-temperature selection hypothesis, several studies of both mammals (e.g., McNab and Morrison 1963;McNab 1979;Hinds and MacMillen 1985;White 2003) and birds Williams 2000, Tieleman et al 2003) have reported lower BMR in hot deserts. However, as noted above, hot deserts also have low precipitation and low primary productivity.…”
Section: Predictors Of Body Mass Bmr and Mmrmentioning
confidence: 93%
“…If variation in environmental temperature leads to variable natural selection on BMR, then it could occur in at least two ways (MacMillen and Garland 1989;Lovegrove 2000Lovegrove , 2003White 2003). First, high temperatures could favor low BMR to avoid overheating and/or for energy or water conservation, given that many habitats with high temperatures also have relatively low primary productivity and water availability (i.e., most deserts).…”
Section: Predictors Of Body Mass Bmr and Mmrmentioning
confidence: 99%
See 2 more Smart Citations
“…Many desert organisms like scorpions, snakes, and lizards burrow and swim effectively in sand [33,34,35,36,37] to escape heat and predators, and hunt for prey [38,39]. It has been hypothesized that many of these animals have evolved morphological adaptations like marked body elongation and limb reduction to deal with deformable terrain [40,41].…”
Section: Introductionmentioning
confidence: 99%